Stone fruit - Lai, Lee 1993- (Fantagraphics Books, Inc., 2021)
"Bron and Ray are a queer couple who enjoy their role as the fun weirdo aunties to Ray's niece, six-year-old Nessie. Their playdates are little oases of wildness, joy, and ease in all three of their lives, which ping-pong between familial tensions and deep-seeded personal stumbling blocks. As their emotional intimacy erodes, Ray and Bron isolate from each other and attempt to repair their broken family ties -- Ray with her overworked, resentful single-mother sister and Bron with her religious teenage sister who doesn't fully grasp the complexities of gender identity. Taking a leap of faith, each opens up and learns they have more in common with their siblings than they ever knew."--Publisher's description
Keywords: Geschlechtsidentität; Nichte; Frau; Homosexualität; Literary studies & criticism; Lesbian couples / Comic books, strips, etc / Fiction; Dysfunctional families / Comic books, strips, etc / Fiction; Sisters / Comic books, strips, etc / Fiction; Sexual minorities / Comic books, strips, etc / Fiction; Gender identity / Comic books, strips, etc / Fiction; Comic